Assessment of Patientsâ€™ Knowledge Toward Total Hip Replacement Home â€" Care - Suad J. Mohamed; Abdullah E. Mecheser (College of Pharmacy University of Baghdad, 2017)
To assess the total hip replacement patientsâ€™ knowledge of home â€" care regarding pain management, medication therapy, wound care, mobility limitation and complications may occur in the post hip replacement surgery, and to assess relationship between some variables such as, age level of education, sex & marital status with home- care knowledge. A descriptive study was used to assess the hip-replacement patient home-knowledge, a purposive sampling of (60) hip-replaced â€"patients were selected from Gazy Alhariri Hospital  (central of surgical profession ) and Alwasity Hospital ( plastic surgery) , the questionnaire  obtains two parts , part one, which included socio-demographical characteristics of the sample and part 2  , which included hip-replacement home-care  knowledge , reliability and validity of the questionnaire were determined . Data were collected through the use of the questionnaire, at the hip application of the interview techniques and review of the hip replacement surgery rehabilitation review literature. Data were analyzed through descriptive and inferential data approach.The result of the study presented that the majority of the study sample were group at age (25-35) years old, female married, housewife with (50%) of patients were at level of primary school education. They were lacking knowledge toward pain management at home and wound care , also discharged with very minimum information and rehabilitation training instruction toward practicing assistive walking and activity device or preventing potential complication such as infection and dislocation , Besides the study revealed a significant relationship between total- hip replacement knowledge toward complication may be occurred and level of education ,which revealed that the educated hip- replaced patients can managing and preventing the complication may occurred better than those not educated.Establishing a special rehabilitation unit in the ward to provide the patients with  a rehabilitation program for training , also to provide them with a booklet or pamphlet illustrating all  formations the patient may need at home. Key words:  Total â€" hip replacement ,  patientsâ€™ knowledge of pain  , patientsâ€™-knowledge of potential complication  , patients' knowledge toward wound ,  patientsâ€™ knowledge of mobility.